2020
DOI: 10.1002/1878-0261.12657
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine‐CREB1‐miR‐373 axis promotes progression of colon cancer

Abstract: The adrenergic system contributes to the stress-induced onset and progression of cancer. Adrenergic fibers are the primary source of norepinephrine (NE). The underlying mechanisms involved in NE-induced colon cancer remain to be understood. In this study, we describe the function and regulatory network of NE in the progression of colon cancer. We demonstrate that NE-induced phosphorylation of cAMP response element-binding protein 1 (CREB1) promotes proliferation, migration, and invasion of human colon cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“… Hu et al (2019) , who looked at breast cancer, displayed that CREB1 exerts oncogenic effect through regulating CREB1/lin28/miR-638/VASP regulatory network. In addition, CREB1 is an oncogene in colon carcinoma ( Han et al, 2020 ). Thus, CREB1 plays a vital role in modulating occurrence and progression of tumors.…”
Section: Introductionmentioning
confidence: 99%
“… Hu et al (2019) , who looked at breast cancer, displayed that CREB1 exerts oncogenic effect through regulating CREB1/lin28/miR-638/VASP regulatory network. In addition, CREB1 is an oncogene in colon carcinoma ( Han et al, 2020 ). Thus, CREB1 plays a vital role in modulating occurrence and progression of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that CREB1 plays a vital role in the tumor progression of upper liver cancer [ 37 ]. In addition, CREB1 has also been reported to be directly related to the ability of colon, breast, and gastric cancer to metastasize [ 28 , 38 , 39 ]. These findings showed that CREB1 could serve as a novel biomarker for OV cancer diagnosis and prognosis prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Page 11/21 [21] Several studies have demonstrated that stress-induced activation of the adrenergic system not only promotes the proliferation of cancer cells themselves but also contributes to the metastasis of malignant tumours. [21,22] It has been shown that NE promotes the migration of colon cancer cells by binding to the β2-AR on tumor surface, while propranolol, a β-blocker, prevents the liver metastasis of colon cancer. [23,24] In fact, enteric neurotransmitters are also involved in the remodeling of liver immunity.…”
Section: Discussionmentioning
confidence: 99%